Digital Technology Training for Strengthening Products in MSMEs - Soemardiono, Soemardiono; Asrovianto, Denny (Bisma : Bimbingan Swadaya Masyarakat, 2023)
The purpose of mentoring through digitalization of this technology is to strengthen products in marketing through digital marketing. Through the technology digitalization training approach, this training has an impact on MSMEs in Pepelegi Waru Sidoarjo Village, including knowing, understanding and operating digital marketing in their business. They also have an increase in capacity in product packaging capabilities so that they can easily market products through digital marketing. The existence of this ability, MSME products can be marketed in various media so that they have a wider market.